PENGARUH EKSPOR, PENANAMAN MODAL ASING, DAN UTANG LUAR NEGERI TERHADAP CADANGAN DEVISA DI INDONESIA - Hanna Elmia Putri; Toti Indrawati; Any Widayatsari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of Export, Foreign Investment and Foreign Debt Against Foreign Exchange Reserves in Indonesia. This study uses secondary data obtained from Bank Indonesia and the Central Bureau of Statistics. This research was conducted in the period 1996 to 2015. This study used a descriptive analysis of quantitative and analytical tools used multiple linear regression analysis using SPSS computer application program 20.Our results obtained Exports, Foreign Investment and Foreign Debt By simultaneously affect the foreign exchange reserves in Indonesia with a significance level α = 5% probability of F statistics obtained value <α (0.05) ie 0.000 <0.05. Partially Export positive and significant impact on foreign exchange reserves, the Foreign Investment significant negative effect on International Reserves and Foreign Debt positive and significant impact on foreign exchange reserves. Variations of factors that influence the foreign exchange reserves is explained by exports, the Foreign Investment and Foreign Debt jointly effect of 97.4%. This means that approximately 97.4% of foreign exchange reserves is explained by the variable Exports, Foreign Investment and Foreign Debt.Keywords: Exports, Foreign Investment, Foreign Debt, Foreign Exchange Reserves